2021
DOI: 10.32674/jis.v11is2.3577
|View full text |Cite
|
Sign up to set email alerts
|

Social Value Systems and the Mental Health of International Students During the COVID-19 Pandemic

Abstract: Australian universities are understood to have the highest number of international students per capita worldwide. The sector contributes over $40 billion to the national economy and sustains many thousands of jobs. Despite their importance to the Australian economy and society, international students are often overlooked in mainstream health promotion and support services. Of the many difficulties and hardships international students experience, mental health presents a significant problem. Evidence indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
1
10
1
Order By: Relevance
“…Similar to a recent study among international students in Australian universities where declining mental health was one of the issues reported among students due to the pandemic (Humphrey & Forbes-Mewett, 2021), mental health was the second top non-academic challenge identified in this study. Increasing awareness about counseling and health services available through campus and community organizations is recommended.…”
Section: Non-academic Challengessupporting
confidence: 82%
“…Similar to a recent study among international students in Australian universities where declining mental health was one of the issues reported among students due to the pandemic (Humphrey & Forbes-Mewett, 2021), mental health was the second top non-academic challenge identified in this study. Increasing awareness about counseling and health services available through campus and community organizations is recommended.…”
Section: Non-academic Challengessupporting
confidence: 82%
“…The retention of existing international students, and attraction of new students will be paramount for the future sustainability of global academic institutions. Further, research has identified a need to explore the concerns and experiences of international students during the COVID-19 outbreak [3,21,22]. According to the Student Covid Insights Survey (SCIS) conducted by the Office for National Statistics (ONS) in 2020, the COVID-19 pandemic has affected the mental health and well-being of over 50% of students in higher education in England [23].…”
Section: Introductionmentioning
confidence: 99%
“…Before we look at some further recommendations for the reopening of colleges, some prerequisites must be adopted (Herpich; The Jed Foundation, 2020 ; National Institute of Mental Health and Neurosciences, 2020 ; Borwankar, 2020 ; Humphrey and Forbes- Mewett, 2021 ; Saha et al, 2021 ; Chaturvedi et al, 2021 ; Sustarsic and Zhang, 2021 ; Gomes and Forbes- Mewett, 2021 ). Though colleges/universities are educational institutes, the focus should not be restricted to strategizing only for educational curriculum but also students' mental well-being.…”
Section: Discussionmentioning
confidence: 99%